Does Child Care Pay? Labor Force Participation and Earnings: Effects on Access to Child Care in the Favelas of Rio de Janeiro - Ruthanne Deutsch (Inter-American Development Bank, Office of the Chief Economist, 1998)
This study undertakes an econometric analysis of data on the use of child care services and labor force participation drawn from a survey of 1,720 households in 15 `favelas,` or slums, in Rio de Janeiro. The analysis examines the impact that access to child care services has on female labor force participation and final earnings.
Keywords: 330